2007
DOI: 10.1159/000101335
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Nocturnal Urinary Leptin and Gonadotrophins as Children Progress towards Puberty

Abstract: Background/Aims: Leptin is necessary for normal human pubertal development but its exact role in the period leading up to the onset of puberty has not been defined. This study has assessed the relationship between leptin and gonadotrophin secretion over time as children progress into puberty. Subjects and Methods: Twenty children (13 boys and 7 girls) judged to be close to the initiation of puberty were recruited. Three consecutive first morning urine samples were collected from each subject each month over 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
1
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 60 publications
5
28
1
1
Order By: Relevance
“…In girls, we observed that prepubertal leptin concentrations (Tanner stage 1), when acting as a lead, related to early pubertal LH and FSH concentrations (Tanner stage 2), as observed in both boys and girls by Masqood et al (11). These results imply a temporal relationship between leptin and gonadotropic hormones during early puberty.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In girls, we observed that prepubertal leptin concentrations (Tanner stage 1), when acting as a lead, related to early pubertal LH and FSH concentrations (Tanner stage 2), as observed in both boys and girls by Masqood et al (11). These results imply a temporal relationship between leptin and gonadotropic hormones during early puberty.…”
Section: Discussionsupporting
confidence: 82%
“…Relationships between dependent and independent variables were determined using simple linear regression models. To investigate a timedependent relationship in the sequence of the hormonal changes during puberty, we used the lead/lag technique, which correlates hormones secreted in one stage, with those secreted in the next stage (11). All tests were two-sided and differences were considered significant at P!0.05.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations